ANALISIS HUKUM PENYELESAIAN SENGKETA PELAKU USAHA YANG MENGALAMI PAILIT BERDASARKAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN - M. Ali Mansyur; Rusnaldi Salim (Jurnal Pembaharuan Hukum, 2014)
The growing business in Indonesia, became an issue for consumers when the company no longer walk according to regulations. Now, many companies are bankrupt. When attacked by a corporate bankruptcy , the company was taken over by the curator in accordance with the provisions of the Bankruptcy Act, and will no longer be the owner of his property for a while. This situation makes consumers confused, because there are many consumers who do not understand the bankruptcy problem, because it is at the beginning of the agreement, the companies represented by his agent, almost never explain the bankruptcy problem.Non-litigation settlement through paths made by BPSK in a way Mediation, Conciliation, and Arbitration. Secondly, Corporate Responsibility/business to consumers if the company has been declared bankrupt by way of paying compensation in accordance with a written agreement that has been agreed by both parties. The steps taken to realize the protection of consumers. The suggestions offered are Supervision and guidan c e of the government against the company/business, the written agreement on how to improve the company so that the company has a lot of consumers that can bring higher profits . So the company is not bankrupt because the company either conventional circumstances that do not harm consumers.